Penyidikan Tindak Pidanan Eksploitasi Anak Di Kepolisian Resor Kota Pekanbaru Berdasarkan Undang-Undang Nomor 35 Tahun 2014 Tentang Perubahan Atas Undang-Undang Nomor 23 Tahun 2002 Tentang Perlindungan Anak - Mhd Syukri; Erdianto Effendi; Widia Edorita (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
Chid is the greatest gift to the family, religion, nation, and state. Birth of a child is the forerunner of a new generation which is the successor to the ideals of national stuggle and human resources for national development. To protech the rights of the child is no specific legislation on child pretection money is a law number 35 of 2014 concerning amandments to the law number 21 of 2002 on child protection. One of the safeguards that the investigastion carried pliers investigator on the case child exploitation PPA is used to fulfill the rights of children as victims of crime in the case the investigator must provide services very satisfyingto victims of criminal acts of child exploitation, so that the victim feels right indeed been given to him. The purpose of this thesis, namely: first, to determine the police investigation conducted pekanbaru resort town. Second, obstacles encountered in the process of investigators in overcoming the obstacles that arise in the process of investigation of criminal exploitation of children in the resort city police pekanbaru.This kind of research can be classified into types of socio-juridical studies because in this study the authors conduted a study on in the location or place to learn to give clear and complete picture of the problem under study. Data source used, primary data, secondary data and data tertiary blunting technical in this study with interviews and literature review.The results of research there are three issues that can be inferred. First, that the investigations conducted by the investigator as not fit properly which has been stipulated in the law, so that the absence of a sense of dissatisfaction experienced by the victim or the victim’s family. Second, the obstacles encuntered in the process of investigation is a very difficult obstacle investigators in conducting the investigation, because the perpetrators can ascape, and difficult to ask for information from the victim. Third, the efforts of investigators in the interrogation of obstacles.Advice to investigators to be authors would handle the case against child exploitation, conduct investigations quickly, and soon finds the efforts to overcome obstacles and immediately won doublt such offenses.Keyword: Child, Exploitation, Investigation, Crime